PENYIDIKAN TERHADAP PENYEDIA JASA PROSTITUSI MELALUI MEDIA INTERNET DI WILAYAH HUKUM POLISI DAERAH METRO JAYA - Putri Widjayanti; Mexasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
During the last five years range (2009-2014) there were four cases of prostitution services provider via the Internet which handled by the Polda metro jaya. In 2009 the AT suspect who manages the website with the domain name www.wanita18theclub.com. In December 2010, the Jakarta Police succeed to capture VL and WD that manages facebook account (kine kekasih gelapku) and www.bluefame.com website. In 2012 succeed to catch RW carriers website, NA-pimp and HD-field operations that manage the website with the domain name www.krucil.net, www.bintangmawar.net, www.semprot.net. They (RW carriers website, NA-pimp and HD-field operations). In March 2014, SL SY and the US suspect was captured by managing facebook account Andi Hotel Room.Investigation on prostitution services provider via the Internet is done by cyber part of polda metro jaya's TNCC unit is to track the whereabouts of offenders by tracing the Internet Protocol address ("IP Address") actors based logs IP addresses stored in the server manager web site / homepage used as a means of suspect in prostitution online.Barriers that hold Polda metro jaya in the investigation process is increasingly difficult to conduct criminal investigations against prostitution, and it is difficult to find the real identity of the suspects because all of the suspects using electronic devices also a web site / homepage admin is outside the region Indonesian jurisdiction (such as facebook, google, twitter, yahoo, etc.). Efforts are being made for overcome factors of barriers is to enforce and implement laws and regulations that apply properly and optimally, improve the means and facilities to make it easier for law enforcement in combating prostitution service provider via the Internet, and increase public awareness in law enforcement and applying eastern culture in life.Keywords : investigation-provider-prostitution-via internet.